MODEL KONSEPTUAL FAKTOR PENDORONG NIAT SEBAGAI FASILITAS PENGUMPULAN MINYAK GORENG BEKAS SEBAGAI INISIASI JARINGAN REVERSE LOGISTICS - Budijati, Siti Mahsanah; Astuti, Fatma Hermining; Jatiningrum, Wandhansari Sekar; Rini, Poppy Laksita (Fakultas teknik Universitas Muhammadiyah Jakarta, 2024)
The driving factors of intentions as a used cooking oil collection facility: a conceptual model. The reverse logistics (RL) flow characteristics include scattered supply sources and uncertain supply quantities. This characteristic also applies to the flow of used cooking oil, which is one of the ends of used products that can be managed through RL activities. In addition, there is no regular mechanism for collecting used cooking oil from food service businesses and households. The current collection process is handled by third parties whose main aim is for economic gain. On the other hand, to create a sustainable cooking oil supply chain that provides economic benefits and realizes environmental sustainability and social responsibility, it is necessary to take responsibility for food service business actors as producers of used cooking oil. This form of responsibility can be in the willingness to serve as a facility for collecting used cooking oil. The willingness of a food service business to serve as a collection facility is, of course, influenced by certain factors. This research proposes a conceptual model of the driving factors for the willingness of food service businesses to serve as used cooking oil collection facilities. This conceptual model was built based on a literature review and adjustments to the current RL flow conditions of the used cooking oil. The conceptual model formed can be used as a basis for empirical research on food service business actors.